PSO Based Traffic Optimization Approach for Railway Networks - Yaman, Orhan; Karakose, Ebru; Karakose, Mehmet (Ieee, 2018)
In large cities, most people use more than one vehicle of transportation per day. With the increase of transportation vehicles, traffic problems also arise. Railway transportation is an indispensable type of transportation for crowded cities. In this study, a method based on Particle Swarm Optimization is proposed for railway traffic. On the one-way and two-way railway line, the trains are waiting for each other as they move. In this study, a method was developed to reduce the waiting time of trains. A simulation environment was established for the implementation of the developed method. A simulation with 12 stations on a one-way and two-way railway with a length of 340 km was developed and 11 trains were used. In the proposed method, the objective is to minimize the waiting times of the trains by creating the best voyage plan.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Railway timetable; Railway scheduling; Rail transportation; Railway traffic optimization; PSO algorithm